An event of underground predation on a wintering caudate amphibian by a carabid beetle - Bernard, Rafal; Samoląg, Juliusz (Entomologica Fennica, 2014)
Pterostichus niger (Coleoptera: Carabidae) preying on Lissotriton vulgaris (Caudata: Salamandridae) in complete darkness and fairly low ambient temperatures was recorded in mid-winter in the underground fortifications near Strzaliny, NW Poland, confirming the occurrence of the predation on small caudate amphibians by carabid beetles in natural conditions. The long but successful predatory event, being a result of sharing the same shelter, revealed the opportunistic predispositions of that generalist predator in a situation in which its typical prey was absent. This suggested that small amphibians may be a source of food for carabids, even for only moderately large species, in late autumn and winter shelters.